(untitled) (Web of Teachers: Inderscience Research, 2025)
In modern society, digital technologies are fundamentally changing the education system. In particular, artificial intelligence (AI) is becoming an important component of the educational process. This article highlights the role, capabilities and prospects of artificial intelligence in the field of pedagogy. The author analyzes the role of AI tools in personalizing the educational process, identifying student abilities, monitoring the educational process, and reducing the teacher’s workload. Practical examples show how artificial intelligence-based platforms (for example, adaptive learning systems, virtual assistants, analytical programs) affect the quality of education. At the same time, attention is also paid to the dangerous aspects of technology, namely the withdrawal of the human factor, the protection of personal data, ethical and legal issues. At the end of the article, the author’s personal suggestions and real recommendations for the effective implementation of artificial intelligence are given. In general, the article provides a deep analysis of the relationship between artificial intelligence and education, which is relevant today, and shows what opportunities this technology will open up in the future. The topic is approached from a pedagogical point of view.